A Conservative Approach for the Fast Deflagration Analysis in the Containment With GASFLOW-MPI - Yabing, Li; Xianghui, Lu; Peng, Chen; Deyang, Xu (Frontiers in Energy Research, 2022)
The nuclear regulation authorities of many countries require that the containment remains its integrity for a local hydrogen risk during any possible accident conditions. Therefore, the combustion consequence should be analyzed to demonstrate that the containment integrity is not being challenged for the hydrogen risk when the flame acceleration risk cannot be safely ruled out. Considering the uncertainties of both the combustion model and severe accident analysis, the criteria and experimentally based combustion (CREBCOM) model is adopted to provide a conservative result for pressure and the thermal load for combustion analyses in this study. Firstly, the CREBCOM is developed in the GASFLOW-MPI code and validated with the RUT experiment. The result shows that the CREBCOM model can provide a reliable overpressure for the choking regime combustion. Then, this model is adopted for the hydrogen safety analysis for the Advanced Pressurized Water Reactor (PWR) 1000. The hydrogen distribution is calculated with the mass and energy release obtained from severe accident analysis, from which, the most unfavorable ignition time and location is selected. The result of the CREBCOM model is compared with that of the turbulent flame closure model, which is a commonly used model for combustion analysis in containment safety. The results show that the CREBCOM model can provide a conservative prediction for the pressure and thermal load of combustion. Therefore, the CREBCOM model with the sonic flame assumption is applicable for the FA risk analysis in a local compartment for nuclear containments where a sonic deflagration cannot be safely excluded and manages to obtain a conservative pressure and thermal load for further evaluation on the containment integrity.